Existence, attractivity and controllability results for integro-differential equations with state-dependent delay - MEDJADJ, Imene; SALIM, Abdelkrim; BENCHOHRA, Mouffak (Studia Universitatis Babeș-Bolyai Mathematica, 2026)
The objective of our research is to investigate the existence, attractivity and controllability of solutions for integro-differential equations with state dependent delays. We employ a fixed point theorem to establish the existence of these solutions, while also utilizing the concept of measures of noncompactness. In the last section, we give an example to show that the assumed conditions can be verified and to illustrate our results. Mathematics Subject Classification (2010): 34G20, 34K20, 34K30. Received 02 July 2025; Accepted 23 April 2026.